Potensi Tumbuhan Xanthostemon novoguineensis Valeton (Myrtaceae) dalam Fitoteknologi - Raynard C. Sanito (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
This article is essential in a further analysis that related with potential feasibility function of Xanthostemon novoguineensis in phytotechnology from one of an endemic plant in Papua, particularly in the remediation of polluted environment and the phytostructure of open green space area. This review aims to analyse the potential of this plant based on literature review and compare each research results towards some species from Myrtaceae family. X. novoguineensis may be cultivated on an open green space area in Papua due to complying suitable requirements. Those requirements are namely ecology function as a source of insect diets, social-cultural functions in represent culture, the the relationship among Papuan Ethnic and their nature, and aesthetic functions due to its beautiful flower. In addition, the plant has a potential in phytoremediation of polluted environment due to its adaptation ability in a dry soil condition. As the comparison, the phytostructure of open green space area context, X. chrysanthus has been cultivated on a public and private open green space area in Malaysia and Singapore. It has an important role as ecology function due to provide the source of food to many birds species undirectly. Owing to make the city landscape greater, the flower of X. chrysanthus, which has conspicuously and magnificently yellow colour, is a suitable plant to be cultivated. Furthermore, in the remediation assessment of polluted environment, X. chrysanthus has the abilities in adaptation on the dry environment. The range levels acid (pH) of soil are 2-2.5. Interestingly, X. melanoxylon, which is an endemic species from Solomon Island, is growth naturally in an ultrafamic soils, consist of a high concentration of chromium, nickel, and magnesium. It also has a low degree of plants biodiversity. Therefore, according to X. chrysanthus and X. melanoxylon, X. novoguneensis has a tremendous potential as a candidate in Phytostructure and Phytoremediation. However, the further investigation is required to reveal the potential and the conservation challenge of this plant in Papua. Key words: phytoremediation, phytostructure, open green space area, X. chrysanthus, Potential.